CRATONIC MANTLE ROOTS, REMNANTS OF A MORE CHONDRITIC ARCHEAN MANTLE? - Francis D. (My University, 2003)
The Earth's continents are cored by Archean cratons underlain by seismically fast mantle roots descending to depths of 200 + km that appear to be both more refractory and colder than the surrounding asthenospheric mantle. Low-temperature mantle xenoliths from kimberlite pipes indicate that the shallow parts of these cratonic mantle roots are dominated by refractory harzburgites that are very old (3 + Ga). A fundamental mass balance problem arises, however, when attempts are made to relate Archean high-Mg lavas to a refractory restite equivalent to the refractory lithospheric mantle roots beneath Archean cratons. The majority of high-Mg Archean magmas are too low in Al and high in Si to leave behind a refractory residue with the composition of the harzburgite xenoliths that constitute the Archean mantle roots beneath continental cratons, if a Pyrolitic primitive mantle source is assumed. The problem is particularly acute for 3 + Ga Al-depleted komatiites and the Si-rich harzburgites of the Kaapvaal and Slave cratons, but remains for cratonic harzburgites that are not anomalously rich in orthopyroxene and many Al-undepleted komatiites. This problem would disappear if fertile Archean mantle was richer in Fe and Si, more similar in composition to chondritic meteorites than the present Pyrolitic upper mantle of the Earth. Accepting the possibility that the Earth's convecting upper mantle has become poorer in Fe and Si over geologic time not only provides a simpler way of relating Archean high-Mg lavas to the lithospheric mantle roots that underlie Archean cratons, but could lead to new models for the nature Archean magmatism and the lower mantle sources of modern hot-spot volcanism.
Keywords: Archean; Craton; Lithosphere; Mantle; Root; Chondrite; Precambrian::Archean; Докембрий::Архей